(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
The cinematic image itself could serve as a medium that can represent a conceptualization of time thanks to its formal elements, which temporalize space and spatialize time, rendering duration and the experience of passing time. Taking into account Frammartino’s cinema “Il dono” (2003), “Le quattro volte” (2010) and “Alberi” (2013), this essay aims to highlight how particular strategies to frame the passing of time, in line with the durational tendency in structural experimental cinema and its acute manifestation in “slow” contemporary films, encourage a contemplative spectatorial practice. This invites the viewer to wander within the frame and to focus on details which would otherwise remain veiled in a conventional form of narration.